Measurement of CP observables in B± → D(*)K± and B± → D(*)π± decays using two-body D final states; Journal of High Energy Physics; Vol. 2021, iss. 4 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen